Aggression profiles of incarcerated Malaysian male murderers - Mohammad Rahim Kamaluddin,; Azizah Othman,; Khaidzir Ismail,; Geshina Ayu Mat Saat, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Criminological and psychological researches have highlighted aggressive behavior as the basic ingredient of violent crime, including murder. Increased concerns about the rate of murder in Malaysia have called for studies examining aggression profiles of the Malaysian murderers. The present study intends to explore the aggression profiles of Malaysian male prisoners convicted of murder, utilizing Buss and Perry’s Four Structure Aggression Model. A cross-sectional methodology was adapted as a research design of the present study. A guided self-administered questionnaire was distributed among 71 Malaysian male prisoners convicted of murder using purposive sampling method. The entire aggression profiles are assessed using Aggression Questionnaire-12 items (AQ-12). Descriptive item analyses were carried out to elicit the level of responses for each item in the AQ-12 while bivariate analyses were used to ascertain associations among aggression subscales. The aggression profiles indicated that the mean score of anger (8.10, SD = 2.93) was higher than other forms of aggression traits. The least mean score was noted for verbal aggression (6.24, SD = 2.45). Among the respondents, 54.9% of them scored above the mean score (8.10) for anger subscale. This was followed by 52.1% who scored above the mean score (7.77) for physical aggression subscale. The correlations among all the aggression subscales had indicated positive and significant associations which in turn, may enable it to be a platform to inspire other researches in this field. In conclusion, this ground-breaking study among male murderers has successfully explored aggression profiles using AQ-12.